(untitled) - Fahey, Thomas D. (Boston, 2004)
Fit and Well offers the best text and teaching package to help students incorporate fitness and wellness into their daily lives. With an emphasis on personal responsibility and behavior change, this text provides accurate, up-to-date information on the five components of health-related fitness, as well as coverage of nutrition, stress, substance abuse, chronic diseases, and injury prevention and personal safety.
Keywords: Physical fitness,Health,Rèn luyện thể chất,Sức khỏe